PENGEMBANGAN MODAL SOSIAL MAHASISWA LUAR JAWA DI UNIVERSITAS SLAMET RIYADI - Damayanti, Christy (Transformasi, 2017)
Social capital is a capital that has important role in supporting individuals in interacting with the society. The academic achievement and success of Slamet Riyadi University students from outside Java is highlydetermined to develop social capital that affect the level of trust, social interaction, and reciprocalquality. This study examines how students outside Java at Slamet Riyadi University Surakarta developtheir social capital. As a qualitative research, this study obtained data through observation, interviews,and disscusion group forums. The theory used in this research is the theory of social capital foreducation. The conclusion of this study is the factor that strongly hinder the development of social capitalof students from outside Java at Slamet Riyadi University Surakarta is the taste of food and language.Furthermore, to develop social capital is needed role of institutional support of Slamet Riyadi Universityand community institutions.Keywords: social capital, student, difference